ANALYSIS OF METHODOLOGICAL APPROACHES TO PROBLEM SOLVING SKILL IN MATHS TEXTBOOKS FOR GRADES 5-6 - Krastiņa, Elfrīda; Sondore, Anita; Drelinga, Elga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
One of the most important cross-cutting skills in the competence approach, which is developed in learning mathematics, is problem-solving. Solving mathematics word problems with practical content includes both text analysis, visualization of content, planning, and searching for different solution steps, argumentation of one’s opinion, solution design, as well as research. During his working life Professor J. Mencis (senior) has developed a methodological system of word problems. What is the offer of other authors? The aim of the article is to analyse the implementation of methodological approaches by various authors in the 5-6th grade maths textbooks, which develop the problem-solving skill, in order to find out the strengths and weaknesses of these methodological solution.